Percutaneous, non-operative radio frequency ablation for haemostasis of ruptured hepatocellular carcinoma - Manikam, J.; Mahadeva, S.; Goh, K.L.; Abdullah, B.J. (2009)
Spontaneous rupture and hemorrhage is a devastating complication of hepatocellular carcinoma (HCC). Results from current therapeutic modalities remain varied. Recent development of percutaneous radiofrequency ablation (RFA) in the management of this condition has shown promise. We describe 2 cases of ruptured HCC in which non-operative, percutaneous radio frequency ablation (RFA) was successful in achieving hemostasis. The advantageous of RFA over other interventional techniques in the management of ruptured HCC are discussed.